Aberrant Origin of the Distal Anterior Cerebral Artery from the Middle Cerebral Artery Related to Obstruction of Bilateral Proximal Anterior Cerebral Arteries: A Case Report - Kwak, Hyo Sung; Chung, Gyung Ho; Hwang, Seungbae (Current Medical Imaging, 2023)
Background: Aberrant origin of the distal anterior cerebral artery (ACA) arising from the middle cerebral artery (MCA) is extremely rare. Case Presentation: A 74-year-old woman with a sudden onset of left-sided weakness was admitted to the emergency department. Angiography revealed an unusual course of the distal ACA originating from the MCA with bilateral obstruction of the proximal segment of the ACA and simultaneous occurrence of infarction in the ACA and MCA territories. Conclusion: Knowledge of a rare vascular variation or anomaly could help understand brain imaging, which has an unusual involvement of vascular territories, performed in patients with acute ischemic stroke.
Keywords: CT